Arabic Calligraphy as a Pedagogical Tool in Increasing Aesthetic Appreciation of Arabic Language Education Study Program Students - Syukron, Akhmad Aufa; Arifudin, Muhammad; Lina, Ayda Farah; Fadhlurrohman, Fikri; Baharun, Mohamad Nor Amin Samsun (al-Ittijah: Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2026)
This study aims to analyze the utilization of Arabic calligraphy as a pedagogical tool to enhance aesthetic appreciation among students in the Arabic Language Education Program. Employing a descriptive qualitative approach, the research explores the implementation of calligraphy-based learning, its impact on students’ aesthetic sensitivity, and the supporting and inhibiting factors influencing its effectiveness in higher education settings. The findings reveal that Arabic calligraphy plays a significant role in enriching aesthetic understanding through learning activities that integrate visual, linguistic, and spiritual dimensions. Students engaged in calligraphy practice demonstrate improved accuracy, creativity, and a deeper appreciation of the artistic qualities inherent in Arabic script. Supporting factors identified include cultural relevance, lecturer competence, and students’ intrinsic interest, while key obstacles involve limited facilities, restricted instructional time, and the tendency to rely on instant digital methods. Overall, the study highlights the importance of integrating calligraphy into the Arabic language education curriculum to foster aesthetic competence and strengthen students’ professional character in the modern era.